The Effectiveness of Using Virtual Reality-Based Virtual Laboratories in the Internet of Things Course - Sri Safiatuddin; Rustam Asnawi (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to determine the effectiveness of using Virtual Reality-Based virtual laboratories on student learning outcomes in the Internet of Things Course in the Electrical Engineering Study Program, the average difference in student learning outcomes through the use of Virtual Reality-Based virtual laboratories in the Internet of Things Course in the Engineering Study Program Electrical Engineering, and student learning motivation through the use of Virtual Reality-Based virtual laboratories in the Internet of Things Course in the Electrical Engineering Study Program. This research is an experimental research approach that will be used is Quasi Experimental Design with the form of Nonequivalent Control Group Design. The validation test was carried out by measurement experts for post-test and pre-test questions, each aspect was tested by two experts. The results of the study show the effectiveness of using Virtual Reality-Based virtual laboratories to improve student learning outcomes in the Internet of Things Course in the Electrical Engineering Study Program. The increase in student learning outcomes analyzed using N-gain in the experimental class obtained an average value of 0.65 including the medium category, and the average N-gain for the control class was 0.15 in the low category. Meanwhile, the average difference in student learning outcomes through the effectiveness of using Virtual Reality-Based virtual laboratories in the Internet of Things Course in the Electrical Engineering Study Program is significantly and significantly different. The results of the experimental class data analysis obtained the t_count > t table value, namely 8,351 > 2,003 and the Sig. (2-tailed) 0.005 <0.05, then Ha is accepted, meaning that there is a difference in the average student learning outcomes after using a virtual reality-based virtual laboratory in the internet of things course in the Electrical Engineering Study Program. Student motivation through the use of Virtual Reality-Based virtual laboratories in Internet of Things Courses in the Engineering Study Program can increase very well